Determinants and measures of export performance: Comprehensive literature review - Elena Beleska-Spasova (Journal of Contemporary Economic and Business Issues, 2014)
As one of the key indicators of the firm's ability to leverage successfully its resources and capabilities in the international context, export performance has been one of the most extensively studied phenomena. A plethora of studies have been conducted pertaining to provide better understanding of the factors (firm- or environment-specific) and behaviours (e.g., export strategy) that make exporting a successful venture. Following a comprehensive literature review undertaking in this study the current state of the export performance literature could be summarised as (i) methodologically fragmented in that there is a variety of analytical and methodological approaches, (ii) conceptually diverse, a large number of determinants have been identified as having direct or indirect influence on the firm's export performance, and a large number of indicators have been used to conceptualise and operationalise the export performance measures, and (iii) inconclusive, the studies have produced inconsistent results of the impact of different determinants on export performance.
Keywords: F23; 330; export performance; determinants; measures